Marketing and Management Analysis of Pilgrimage Tourism in a Selected Area in the Czech Republic - Pavel Tvrzník; Zdeněk Málek; Katarína Mrkvová; Miroslav Fišera; Zdeněk Konečný; Darina Eliašová (Communications of International Proceedings, 2020)
Tourism is one of the most developing economic sectors, one of its developing forms being pilgrimage tourism. Pilgrimages and visits to sacred monuments are among the oldest forms of travelling, which have been developing for over a thousand years. In this report we analyse the positive and negative marketing aspects of this form of tourism for a selected monument – bazilika Navštívení Panny Marie na Svatém Kopečku (the Basilica of the Visitation of the Virgin Mary on the Holy Hill) near the town Olomouc, which is on the list of cultural monuments of the Czech Republic. The conclusions summarize the results of the analyses and generalize them for practical application in the frame of pilgrimage tourism. Selected conclusions may be generally applicable in order to increase the tourism of the area with a minimum of negative impacts, which may be an accompanying phenomenon of increasing tourism.
Keywords: Pilgrimage Tourism; Marketing Analyses; Marketing Mix; Strategy of Further Development.